Pengaruh Ekstrak Alga Merah (Kappaphycus alvarezii) terhadap Jumlah Total Bakteri dan Nilai Organoleptik Ikan Kembung (Rastrelliger sp.) [ The Effect of Red Algae Extract (Kappaphycus alvarezii) against the Total Number of Bacteria and Organoleptic Value of Mackerel (Rastrelliger sp.)] - Wahju Tjahyaningsih; Dyo Maliki Hakim; Sudarno Sudarno; Annur Ahadi Abdillah (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Mackerel (Rastrelliger sp.) is a kind of fish that have high economic value and good nutrition but susceptible to decay. People often to use formaldehyde as a preservative so that the fish does not quickly to decay. The use of formaldehyde could be replaced by natural ingredients that contain antibacterial compounds, one of which is Kappaphycus alvarezii. This study aims to determine the effect of red algae extract (K.alvarezii) against the total number of bacteria and organoleptic value of mackerel (Rastrelliger sp.). The research design that done in this study is Completely Randomized Design (CRD). The treatments that given are immersion of mackerel in a solution of extract of K. alvarezii with a concentration of 0 ppm, 600 ppm, 700 ppm, 800 ppm and 1% solution of formaldehyde with four repetitions in each treatment. Data analyzes using Analysis of Variants (ANOVA) and followed by Duncan's Multiple Range Test to determine differences between treatments. The results showed that the extract of red algae (K.alvarezii) at a concentration of 0 ppm, 600 ppm, 700 ppm and 800 ppm significantly (p <0.05) against the total number of bacteria of mackerel (Rastrelliger sp.). The ability of extract of K. alvarezii at a concentration of 800 ppm equivalent to the ability of formaldehyde as an antibacterial ingredient in mackerel. K.alvarezii extract could inhibit the growth of bacteria but have not been able to maintain the quality of mackerel based on organoleptic test.